Synthesis and characterization of new schiff bases derived from benzaldehyde with o-phenylenediamine and1,3-diaminopropane and their Ni(II), Cu(II), Zn(II) and Co(II) complexes / Mazlin Mohideen - Mohideen, Mazlin (2007)
Two new Schiff base ligands are prepared by condensation reaction of benzaldehyde with o-phenylenediamine and 1,3-diaminopropane in the ratio of 2:1. The complexes of two Schiff bases, bis(benzaldehyde)o-phenylenediamine (baOPD) and bis(benzaldehyde)1,3-diaminoprapane (baprop) with Ni(II), Cu(II), Zn(II) and Co(II) have been successfully prepared. The metal complexes are prepared by the direct method in the ratio of 1:1 (baOPD/baprop : metal) and the template method in the ratio 2:1:1 (benzaldehyde : OPD/1,3-diaminopropane : metal). Elemental analysis data, and magnetic susceptibility values have been obtained, IR and 1H NMR spectral studies have been carried out to suggest tentative structures for the characterization of the complexes and ligands. The results suggest that the direct method is better than template method for complexation and the Schiff bases are bidentate ligands (NN) coordinating through the azomethine nitrogens.